Analisis Faktor-Faktor Yang Dipertimbangkan Konsumen Berbelanja Di Sate Taichan Kampoeng Palu - Nilah Karnillah Putri; Zakiyah Zahara; Ponirin; Fera (Cattleya Darmaya Fortuna, 2024)
The purpose of this research is to determine the factors that consumers consider when shopping at Sate Taichan Kampoeng Palu. This type of research uses a qualitative descriptive method with the aim of describing the situation in the field. Data was collected from 20 informants using interview, observation and documentation techniques with a sample of owners, several employees and several consumers. The research results show that the 7P marketing mix strategy analysis (Product, Price, Place, Promotion, People, Process, Physical Evidence) has an important role in selling Sate Taichan Kampoeng Palu products.